Optical image encryption based on quantum walks. (March 2021) - Abd-El-Atty, Bassem; Iliyasu, Abdullah M.; Alanezi, Ahmad; Abd El-latif, Ahmed A.
Highlights: A new optical encryption approach based on quantum walks and DRPE technique is proposed. Alternate Quantum Walks (AQW) is utilized in two encryption stages for security purposes. AQW is adapted to generate two random masks for the DRPE process. Outcomes of simulation-based experiments of demonstrated the efficacy of the proposed approach The results provide impetus to consider its use in applications in modern optical cryptosystems. Abstract: In this paper, we propose a new optical encryption approach based on quantum walks and double random phase encoding technique. Quantum walks have been proven as an excellent tool for designing modern cryptographic mechanisms due to its ability to resist probable attacks from both digital and quantum computers. In the proposed approach, we use the alternate quantum walks (AQW) at two encryption stages. First, inner encryption and encoding by double random phase encoding (DRPE) which executed using permutation followed by substitution. Furthermore, AQW is adapted to generate two random masks for the DRPE process. Simulation-based validation of our proposed technique, including correlation, histogram, sensitivity, key space as well as noise and data loss analysis provide impetus to consider its use in applications in modern optical cryptosystems.